2021
DOI: 10.1051/0004-6361/202039366
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared photometry of the T Tauri triple system with kernel phase interferometry

Abstract: Context. T Tauri has long been the prototypical young pre-main-sequence star. However, with increasing resolution and sensitivity, T Tauri has now been decomposed into a triple system with a complex disk and outflow geometry. Aims. We aim to measure the brightness of all three components of the T Tauri system (T Tau N, T Tau Sa, and T Tau Sb) in the mid-infrared in order to obtain photometry around the ∼9.7 μm silicate feature. This allows us to study their variability and to investigate the distribution of du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This pipeline is based on the XARA ‖ package [18,25,26] and performs bad pixel corrections, windowing, and subpixel re-centering prior to extracting the kernel phases. Finally, the kernel phases of the science target were calibrated with Karhunen-Loève decomposition [22,27,28,29] using the two point-source reference stars as calibrators and detection limits were computed with fouriever. We note that in principle, any of the three KPI targets could have been used as the science target here.…”
Section: Niriss Ami and Kpimentioning
confidence: 99%
“…This pipeline is based on the XARA ‖ package [18,25,26] and performs bad pixel corrections, windowing, and subpixel re-centering prior to extracting the kernel phases. Finally, the kernel phases of the science target were calibrated with Karhunen-Loève decomposition [22,27,28,29] using the two point-source reference stars as calibrators and detection limits were computed with fouriever. We note that in principle, any of the three KPI targets could have been used as the science target here.…”
Section: Niriss Ami and Kpimentioning
confidence: 99%
“…Both the bootstrapping and the MCMC method yield comparable results and an advantage of the latter is that it can also be used to fit more complex models such as multiple companions simultaneously or geometric disk and ring models to the data (see, e.g., Kammerer et al 2021;Blakely et al 2022).…”
Section: Ind Opt Namementioning
confidence: 99%
“…Similar to angular differential imaging (Marois et al 2006) in classical high-contrast imaging, Laugier et al (2020) also derived self-calibrating angular differential kernel phase observables, but these are more suitable for datasets with larger field rotation than JWST can provide. To measure the photometry of the individual components of the T Tau triple star system at ∼ 10 µm, Kammerer et al (2021) applied KPI to VLT VISIR-NEAR observations in the mid-infrared, demonstrating the feasibility of KPI with instruments such as JWST MIRI. Recently, pioneering work from Pope et al (2021) has shown that automatic differentiation methods can be used to extract kernel phase observables from any differentiable optical system, such as a Lyot coronagraph for instance, which has previously been impossible given that focal plane masks destroy the linearity of the Fourier phase observables.…”
Section: Introductionmentioning
confidence: 99%
“…Such an image is processed as if it were taken by an interferometric array thereby computing an interferometric observable, the kernel phase, which can be used for subsequent model fitting. KPI has been successfully deployed in a number of contexts, including studying brown dwarfs 3 and the prototypical young pre-main sequence system T Tauri, 4 and is a useful way to extend the capability of existing instruments such as NIRISS on JWST. 5 It could also be applied to high-contrast imagers such as GPI 6 which sit behind extreme-AO systems.…”
Section: Introductionmentioning
confidence: 99%